FRI0388 Ussefulnes of Bvas and Ffs at Diagnosis To Predict Survival in Anca Associated Vasculitis (AAV). (15th July 2016) - Solans-Laqué, R.; Rodriguez-Carballeira, M.; Rios, J.; Saez, L.; Fraile, G.; Solanich, X.; Pasquau, F.; Oristrell, J.; Fonseca, E.; Callejas, J.L.; Zamora, M.; del Castillo, M.J.; et al.
Abstract : Background: The Birmingham Vasculitis Activity Score (BVAS), and the Five Factor Score (FFS) at the time of diagnosis have been shown useful to asses prognosis in AAV (1, 2), but few studies have been done comparing these tools to predict survival Objectives: To compare the usefulness of BVAS vs 3, 1996 FFS and 2009 FFS at the time of diagnosis, to predict survival in a large cohort of patients with AAV from Spain Methods: multicenter retrospective-longitudinal study that included patients diagnosed with AAV between Jan1995 and Nov13 in 20 Hospitals from Spain (REVAS Study). Patient survival was assessed by life-table analysis using the Kaplan-Meier method. Statistical analysis was done using SPSS vs21 Results: 455 patients were included: 188 (41.3%) GPA, 167 (36.7%) MPA and 100 (22%) EGPA; 50.8% were men. Mean age at diagnosis was 55.7±17.2 y. ANCA were positive in 86.8% of cases: 35.8% C-ANCA and 51% P-ANCA. Median time to diagnosis was 4 weeks (IQR 10). Median follow-up time was 80 months (IQR 105) for global population. Renal involvement was present in 61.5% of cases, lung involvement in 54.7%, pulmonary-renal syndrome in 16.9%, neurological involvement in 34.5%, and cardiac involvement in 12.7%. ENT was observed in 44.8% of cases and eye involvement in 18.9%. Mean BVAS at diagnosis was 17.7±7.7; 1996FFS was ≤1 in 390 (85.8%) patients, and 2009FFS was ≤2 in 361 (79.4%). All patients received oral corticoids, 342 (75.1%) cyclophosphamide (49.7% IV and 50.3% oral), and 6.6% biological therapy. Dialysis was required in 16.4% of cases. During the follow-up, 39.1% of patients suffered bacterial infections, 9.2% sepsis, 12.7% opportunistic infections and 5.3% neoplasms. One hundred thirty (28.6%) died:74 (44.3%) with PAM, 42 (22.3%) with GPA and 14 (14%) with EGPA (p<0.001). Univariate analysis showed that BVAS, 1996FFS and 2009FFS at diagnosis were significantly related to death (p<0.001). A multifactorial Cox regression analysis including the three activity scores confirmed that all of them were statistically related to survival rate but the stronger predictor of poor prognosis was the 2009FFS with a HR 2.7. This result was confirmed by curve ROC: 2009FFS showed the greater area under the curve (75%), in front of 1996FFS (66%) and BVAS (62%) Conclusions: BVAS and FFS at diagnosis are signifivantly related to survival in AAV, but the stronger predictor of survival is the 2009 FFS. References: Merkel P, Cuthbertson D, et al. Comparison of disease activity measures for ANCA-associated vasculitis. ARD 2009;68:103–6 Guillevin L, Seror R, et al. The Five-Factor Score Revisited Assessment of Prognoses of Systemic Necrotizing Vasculitides. Medicine 2011;90:19–27 Disclosure of Interest: None declared